A new synonymy of Heterocerus fenestratus (Thunberg, 1784) (Coleoptera: Heteroceridae) and its first records for South Hemisphere - Sazhnev, Alexey S. (Zootaxa, 2019)
Based on the examination of the type specimens of Heterocerus subantarcticus Trémouilles, 1999, described from Patagonia, the following synonymy is proposed: Heterocerus fenestratus (Thunberg, 1784) = H. subantarcticus Trémouilles, 1999, syn. nov. The ways of the species penetration into the Southern Hemisphere are discussed.